2006
DOI: 10.1007/s11249-006-9133-5
|View full text |Cite
|
Sign up to set email alerts
|

Nano particles’ behavior in non-Newtonian slurry in mechanical process of CMP

Abstract: Thin fluid film is thought to be formed between the wafer surface and the pad asperity. Hydrodynamic pressure on the surface asperity is periodically generated when particles are passing through it. Fatigue fracture occurs under the effect of periodic pressure, and the fatigue begins from the top to the bottom of the asperity. The removal rate is calculated based on the energy-balance fracture theory. Particle size and its relative velocity are important parameters that affect the polishing effect. Using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this paper, a higher-order boundary element method is used, so the solid angle coefficient changes with the shape of the body surface. It can be determined by a direct method (Teng et al 2006). Sloshing-induced force and moment can be obtained by:…”
Section: Sloshing Flowmentioning
confidence: 99%
“…In this paper, a higher-order boundary element method is used, so the solid angle coefficient changes with the shape of the body surface. It can be determined by a direct method (Teng et al 2006). Sloshing-induced force and moment can be obtained by:…”
Section: Sloshing Flowmentioning
confidence: 99%
“…Most assumed that the sample and the polishing pad are fully separated by a layer of slurry film, as discussed in the review by Terrell and Higgs [1]. A few studies have also analyzed the motion and effects of the abrasive particles in the slurry during CMP, using both statistical [2] and Lagrangian-tracking [3,4] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Their results have shown that the particle size increasing resulted in the increasing of surface roughness. [40] to multiphase 2D model which included particles [94,95]. Some approaches in three-dimensional (3D) CFD models were applied to estimate the non-uniformity and MRR [20].…”
Section: Slurry Flowmentioning
confidence: 99%